An Analysis of Prominent Cultural Values in Indonesian Folktale Tourism Spots through Instagram Caption - Rachmijati, Cynantia; Cahyati, Sri Supiah (E-Journal of Tourism; Volume 10 Number 1 (March 2023)DO - 10.24922/eot.v10i1.96300, 2023)
This paper deals with the phenomenon of famous tourism spot in Indonesia which were empowered by folktale through Instagram, such as: Malin Kundang, Sangkuriang, Roro Jonggrang/Prambanan, Danau Toba, and many more. There were some research addressed the tourism spots, nevertheless there’s lack of research on cultural values of folktales in relation to tourism spots in Indonesia and how its aspects deals with its popularity and its marketing. With the development of social media, e.g. Instagram, it brings culture of tourism spot and literature works together and then uploaded it through series of pictures, captions, and stories. This research aimed to analyse the cultural prominent values of the famous tourism folktale spot in Indonesia and employed qualitative method through content analysis studies. The identification towards the Instagram captions on this research were categorized through cultural aspects based on “Four senses of Culture” by Adaskou, Britten, and Fahsi. Based on the cultural sense proposed, it is found 71.42% aesthetic culture sense, 42.85% sociological culture sense, 28.57% semantic culture sense, and last 14.28% pragmatic culture sense. From these findings it can be concluded that for the Instagram and folklore related content itself, photos alone weren’t enough. Good caption cultural values wise added with appropriate hashtag is the proper way. Eventually, though Pandemic hits many aspect of life including tourism, prominent cultural values in Indonesian folktale tourism spot can be preserved.